Frequency-Adaptive Current Controller for Three-Phase Grid-Connected Converters - Gómez Jorge, Sebastián (2013)
This paper analyzes the behavior of a nonfrequencyadaptive reduced-order-generalized-integrator-based current controller when the grid frequency is subject to variations and proposes a simple method for making it frequency adaptive. The proposed frequency adaptation scheme allows to keep the good performance of the current controller even in the presence of frequency variations. The resulting frequency-adaptive controller has very low computational burden, and it is therefore suitable for low-cost digital-signal-processor implementation.